Substrate Ablation by Multivein, Multiballoon Coronary Venous Ethanol for Refractory Ventricular Tachycardia in Structural Heart Disease. Issue 22 (2nd November 2022) - Valderrábano, Miguel; Fuentes Rojas, Stephanie C.; Lador, Adi; Patel, Apoor; Schurmann, Paul A.; Tapias, Carlos; Rodríguez, Diego; Carlos Sáenz, Luis; Malahjfi, Maan; Shah, Dipan J.; Mathuria, Nilesh; Dave, Amish S.
Abstract : Background: Ablation of ventricular tachycardia (VT) in the setting of structural heart disease often requires extensive substrate elimination that is not always achievable by endocardial radiofrequency ablation. Epicardial ablation is not always feasible. Case reports suggest that venous ethanol ablation (VEA) through a multiballoon, multivein approach can lead to effective substrate ablation, but large data sets are lacking. Methods: VEA was performed in 44 consecutive patients with ablation-refractory VT (ischemic, n=21; sarcoid, n=3; Chagas, n=2; idiopathic, n=18). Targeted veins were selected by mapping coronary veins on the epicardial aspect of endocardial scar (identified by bipolar voltage <1.5 mV), using venography and signal recording with a 2F octapolar catheter or by guidewire unipolar signals. Epicardial mapping was performed in 15 patients. Vein segments in the epicardial aspect of VT substrates were treated with double-balloon VEA by blocking flow with 1 balloon while injecting ethanol through the lumen of the second balloon, forcing (and restricting) ethanol between balloons. Multiple balloon deployments and multiple veins were used as needed. In 22 patients, late gadolinium enhancement cardiac magnetic resonance imaged the VEA scar and its evolution. Results: Median ethanol delivered was 8.75 (interquartile range, 4.5–13) mL. Injected veins included interventricular vein (6), diagonal (5), septal (12), lateral (16), posterolateral (7), and middle cardiac vein (8), covering the entire range of left ventricular locations. Multiple veins were targeted in 14 patients. Ablated areas were visualized intraprocedurally as increased echogenicity on intracardiac echocardiography and incorporated into 3-dimensional maps. After VEA, vein and epicardial ablation maps showed elimination of abnormal electrograms of the VT substrate. Intracardiac echocardiography demonstrated increased intramural echogenicity at the targeted region of the 3-dimensional maps. At 1 year of follow-up, median of 314 (interquartile range, 198–453) days of follow-up, VT recurrence occurred in 7 patients, for a success of 84.1%. Conclusions: Multiballoon, multivein intramural ablation by VEA can provide effective substrate ablation in patients with ablation-refractory VT in the setting of structural heart disease over a broad range of left ventricular locations.